2011
DOI: 10.1182/blood-2010-10-315721
|View full text |Cite
|
Sign up to set email alerts
|

p90RSK2 is essential for FLT3-ITD– but dispensable for BCR-ABL–induced myeloid leukemia

Abstract: IntroductionRSK2 is a Ser/Thr kinase that belongs to a family containing 4 members, RSK1 to 4, all of which are downstream substrates of ERK and play a role in various cellular processes including gene expression, cell cycle, survival, and proliferation. RSK family members share both structural and functional similarities, and are uniquely characterized by the presence of 2 distinct kinase domains, both of which are catalytically functional 1-3 (reviewed in Blenis, 4 Frodin and Gammeltoft, 5 and Anjum and Blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…Recent studies have shown that RSK2 acts as the key regulator for cellular transformation and metastasis by mediating signaling through oncogenic tyrosine kinases (TK; refs. [10][11][12]. As for myeloma, previous studies have suggested the importance of RSK2 signaling associated with fibroblast growth factor receptor 3 (FGFR3) activation by t(4;14) (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that RSK2 acts as the key regulator for cellular transformation and metastasis by mediating signaling through oncogenic tyrosine kinases (TK; refs. [10][11][12]. As for myeloma, previous studies have suggested the importance of RSK2 signaling associated with fibroblast growth factor receptor 3 (FGFR3) activation by t(4;14) (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Our data supports the notion that targeting RSK2 with specific small molecule drugs may represent a potential therapeutic strategy to attenuate metastatic cancer cell invasion and tumor metastasis. We previously demonstrated that targeting RSK2 effectively induces apoptotic cell death and attenuates cell proliferation in t(4;14) FGFR3-positive multiple myeloma cells or FLT3-ITD-positive acute myeloid leukemia cells (29,46). We also showed that RSK specific inhibitors such as fmk might have minimal nonspecific cytotoxicity in human cells (29).…”
Section: Discussionmentioning
confidence: 95%
“…6,7 We found that both BCR-ABL and FLT3-ITD activate RSK2 in human leukemia cells, implying that RSK2 may represent a common downstream signaling node that is responsible for cell proliferation and survival in hematopoietic malignancies associated with leukemogenic tyrosine kinases. 8 Surprisingly however, genetic deficiency of RSK2 did not affect the pathogenesis and progression of myeloproliferative disease induced by BCR-ABL in a murine bone marrow transplant (BMT) assay, indicating that RSK2 is dispensable for BCR-ABL-induced myeloid transformation. In marked contrast, the absence of RSK2 abrogated the ability of FLT3-ITD to induce myeloproliferative disease in the same BMT assay, but rather induced a disease of T-cell ALL.…”
Section: Targeting Rsk2 In Myeloid Leukemiamentioning
confidence: 99%
“…1B). 8,11 Future studies exploring the critical role of RSK2 in FLT3-ITD transformed hematopoietic cells may provide further insights toward developing more effective therapies in FLT3-ITD-associated disease.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%